Arthrobacter enclensis sp. nov., isolated from sediment sample - Dastager, Syed Gulam; Qin, Liu; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)
A novel bacterial strain designated as NIO-1008(T) was isolated from marine sediments sample in Chorao Island India. Cells of the strains were gram positive and non-motile, displayed a rod-coccus life cycle and formed cream to light grey colonies on nutrient agar. Strain NIO-1008(T) had the chemotaxonomic markers that were consistent for classification in the genus Arthrobacter, i.e. MK-9(H-2) (50.3 %), as the major menaquinone, and the minor amount of MK-7 (H-2-27.5 %), MK-8 (H-4-11.6 %) and MK-8 (H-2-10.4 %). anteiso-C-15:0, iso-C-15:0, iso-C-16:0 and C-15:0 were the predominant fatty acids. Galactose, glucose and rhamnose are the cell-wall sugars, and DNA G+C content was 61.3 mol%. Phylogenetic analysis, based on 16S rRNA gene sequencing, showed that the strains were most similar to Arthrobacter equi IMMIB L-1606(T), Arthrobacter chlorophenolicus DSM 12829(T), Arthrobacter defluvii KCTC 19209(T) and Arthrobacter niigatensis CCTCC AB 206012(T) with 98.5, 98.4, 98.0 and 97.8 %, respectively, and formed a separate lineage. Combined phenotypic data and DNA-DNA hybridization data supported the conclusion that strains NIO-1008(T) represent a novel species within the genus Arthrobacter, for which the name Arthrobacter enclensis sp. nov., is proposed. The type strain is NIO-1008(T) = (NCIM 5488(T) = DSM 25279(T)).
Keywords: Arthrobacter; Chorao Island; Marine sediment; Polyphasic

Arthrobacter enclensis sp. nov., isolated from sediment sample (vol 196, pg 775, 2014) - Dastager, Syed Gulam; Liu, Qing; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)

Domibacillus enclensis sp nov., isolated from marine sediment, and emended description of the genus domibacillus - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel red-pigmented bacterial strain, designated NIO-1016(T), was isolated from a sediment sample from Chorao Island, India and was investigated by a polyphasic taxonomic approach. The strain was Gram-reaction-positive, strictly aerobic, motile and catalase-positive and produced spherical to slightly ellipsoidal endospores with subterminal position on swollen sporangia. The genomic DNA G+C content was 46.9 molok. The major fatty acids were anteiso-C-15:0, anteiso-C-17:0, iSO-C-15:0 and C-16:0. The predominant quinones were MK-6 (89.3 %) and MK-7 (8.7 %). The polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol, and an unidentified phospholipid. meso-Diaminopimelic acid (type My) was present in the cell-wall peptidoglycan and the major whole-cell sugars were glucose and ribose. The closest phylogenetic neighbours were identified as Domibacillus robiginosus DSM 25058(T) (98.0% similarity) and Domibacillus indicus DSM 28032(T) (97.2% similarity), other species of the genus Bacillus displayed below 96% similarity. Phylogenetic, physiological, biochemical and morphological differences between strain NI0-1016(T) and its closest neighbours indicate that this strain represents a novel species in the genus Domibacillus in the family Bacillaceae for which the name Domibacillus enclensis sp. nov. is proposed with the type species N10-1016(T) (=DSM 25145(T)=NCIM 5462(T)=CCTCC AB 2011121(T)).

Rhodococcus enclensis sp nov., a novel member of the genus rhodococcus - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel actinobacterial strain, designated, NIO-1009(T), was isolated from a marine sediment sample collected from Chorao Island, Goa, India. Phylogenetic analysis comparisons based on 16S rRNA gene sequences between strain MO-1009(T) and other members of the genus Rhodococcus revealed that strain NI0-1009(T) had the closest sequence similarity to Rhodococcus kroppenstedtii DSM 44908(T) and Rhodococcus corynebacterioides DSM 20151(T) with 99.2 and 99.1%, respectively. Furthermore, DNA-DNA hybridization results showed that R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 20151(T) were 39.5 (3.0%) and 41.7 (2.0%) with strain NIO-1009(T), respectively, which were well below the 70% limit for any novel species proposal. Phylogenetically strain NIO-1009(T) forms a stable clade with and R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 201511 with 100% bootstrap values. Strain NI-1009(T) contained meso-diaminopimelic acid as the diagnostic diamino acid and galactose and arabinose as the cell wall sugars. The major fatty acids were C-16:0, C-18:1 omega 9c, C-16:1(omega 6C and/or omega 7c) and 10-methyl C-18:0. The only menaquinone detected was MK-8(H-2), while the major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside and one unknown phospholipid. The G + C content of the genomic DNA was 66.9 molok. The phenotypic and genotypic data showed that strain NIO-1009(T) warrants recognition as a novel species of the genus Rhodococcus for which the name Rhodococcus enclensis sp. nov., is proposed; the type strain is NIO-1009(T) (=NCIM 5452(T)=DSM 45688(T)).

Bacillus encimensis sp nov isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive, rod-shaped, endospore-forming, aerobic bacterium designated SGD-V-25(T) was isolated from Veraval sediment sample, India. Strain SGD-V-25(T) was capable of growing at 25-50 degrees C (optimum 37 degrees C), pH 6-12 (optimum pH 7.0) and with 0-5 % (w/v) NaCl. The taxonomic position of this strain was deduced using a polyphasic approach and the 16S rRNA gene sequence analysis showed that the isolate belongs to the phylum Firmicutes, forming the cluster with Bacillus badius MTCC 1548(T), with which it shares highest similarity of 99.1 % with 13 nt differences. Other type strains of the genus Bacillus showed less than 96% similarity. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The polar lipid profile of strain SGD-V-25(T) showed the presence of diphosphatidylglycerol, phosphatidylglycerol, phsophoglycolipid and two aminophospholipids. The predominant isoprenoid quinone was MK-7. The major cellular fatty acids were iso-C-15:0, anteiso-C-15:0, anteiso-C-17:0 iso-C-16:0, C-16:1 omega 11c and C-16:0. The genomic DNA G + C content of strain SGD-V-25(T) was 37.6 molok. On the basis of phenotypic characteristics, phylogenetic analysis and DNA-DNA hybridization, strain SGD-V-25(T) could be clearly distinguished from closely related members of the genus Bacillus, and the name Bacillus encimensis sp. nov., is proposed to accommodate this strain. The type strain is SGD-V-25(T) (= NCIM 5513(T)=DSM 28241(T)).

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Bacillus cellulasensis sp nov., isolated from marine sediment - Mawlankar, Rahul R.; Thorat, Meghana N.; Krishnamurthi, Srinivasan; Dastager, Syed Gulam (Archives of Microbiology, 2016)
A novel bacterial strain NIO-1130(T) was isolated from sediment sample taken from Chorao Island, Goa Province, India, and subjected to a taxonomic investigation. The strain was Gram-positive, aerobic, and motile. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and strain NIO-1130(T) showed highest sequence similarity with Bacillus halosaccharovorans DSM 25387(T) (98.4 %) and Bacillus niabensis CIP 109816(T) (98.1 %), whereas other Bacillus species showed < 97.0 % similarity. Tree based on gyrB gene sequence revealed that strain bacillus group. The major menaquinone was MK-7 and the predominant cellular fatty acids were iso-C-15:0, anteiso-C-15:0, iso-C-17:0, and anteiso-C-17:0. The strain showed a DNA G+C content of 39.9 mol%. DNA-DNA hybridization studies revealed that strain NIO-1130(T) exhibits 70 % similarity with Bacillus halosaccharovorans DSM 25387(T) and Bacillus niabensis CIP 109816T. On the basis of physiological, biochemical, chemotaxonomic and phylogenetic analyses, we consider the isolate to represent a novel species of the genus Bacillus, for which the name Bacillus cellulasensis sp. nov., is proposed. The type strain is NIO-1130(T) (=NCIM 5461(T) = CCTCC AB 2011126(T)).
Keywords: Bacillus sp; Cellulase; Marine sediment; Polyphasic taxonomy

Reclassification of bacillus isronensis shivaji et al. 2009 as solibacillus isronensis comb. nov and emended description of genus solibacillus krishnamurthi et al. 2009 - Mual, Poonam; Singh, Nitin Kumar; Verma, Ashish; Schumann, Peter; Krishnamurthi, Srinivasan; Dastager, Syed Gulam; Mayilraj, Shanmugam (International Journal of Systematic and Evolutionary Microbiology, 2016)
An investigation into the taxonomic position of Bacillus isronensis MTCC 7902(T) revealed that the strain shares a common phylogenetic lineage with Solibacillus silvestris MTCC 10789(T). It displays considerable overlap in phenotypic properties with the genus Solibacillus, including endospore shape and position, oxidase and catalase activities, presence of iso-C-15 : 0, C-16 : (1)omega 7c alcohol and iso-C-17 : 1 omega 7c as major cellular fatty acids, A4 alpha-type cell-wall peptidoglycan, polar lipids and menaquinone pattern. These features reinforce the findings of molecular phylogenetic analyses based on 16S rRNA gene, gyrB gene and 16S-23S internal transcribed spacer (ITS) region sequences and, in line with the recommendations of Kampfer et al. [Int J Syst Evol Microbiol 56 (2006), 781-786], provide justification for the transfer of Bacillus isronensis from the genus Bacillus to Solibacillus as Solibacillus isronensis comb. nov. The type strain is B3W22(T) (=MTCC 7902(T) =DSM 21046(T) =JCM 13838(T)). An emended description of the genus Solibacillus is also provided.

Domibacillus mangrovi sp nov and domibacillus epiphyticus sp nov., isolated from marine habitats of the central west coast of India - Verma, Ashish; Ojha, Anup Kumar; Dastager, Syed G.; Natarajan, Rameshkumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (International Journal of Systematic and Evolutionary Microbiology, 2017)
While studying culturable bacterial diversity in different marine habitats of the central west coast of India, two novel Gramstain-positive, strictly aerobic, motile, endospore-forming and rod-shaped bacterial strains designated as SAOS 44(T) and SAB 38(T) were isolated from mangrove sediment soil and the surface of a macroalga, respectively. The strains were taxonomically characterized by using a polyphasic approach and genomic methods. The phylogenetic analysis based on 16S rRNA gene sequencing placed the strains firmly in the genus Domibacillus and were most closely related to Domibacillus antri KCTC 33636(T). The predominant fatty acids were iso-C-15 : 0 and anteiso-C-15 : 0. The major polar lipids were diphosphatidylglycerol and phosphatidylglycerol in addition to an aminophosphoglycolipid. MK-6 was the only respiratory quinone. The range of values of digital DNA-DNA hybridization (19.2-24.9 %) and the ortho-average nucleotide identity (74.1-81.4 %) among strains SAOS 44(T), SAB 38(T) and other Domibacillus species clearly supports their status as a distinct and novel species for which the names Domibacillus mangrovi sp. nov. SAOS 44(T) (=DSM 100930(T)=KCTC 33820(T)=MTCC 12571(T)) and Domibacillus epiphyticus sp. nov. SAB 38(T) (=DSM 100929(T)= KCTC 33830(T)=MTCC 12575(T)) are proposed, respectively.

Examination into the taxonomic position of Bacillus thermotolerans Yang et al., 2013, proposal for its reclassification into a new genus and species Quasibacillus thermotolerans gen. nov., comb. nov. and reclassification of B. encimensis Dastager et al., - Verma, Ashish; Pal, Yash; Khatri, Indu; Ojha, Anup Kumar; Gruber-Vodicka, Harald; Schumann, Peter; Dastager, Syed Gulam; Subramanian, Srikrishna; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
Two novel Gram-staining positive, rod-shaped, moderately halotolerant, endospore forming bacterial strains 5.5LF 38TD and 5.5LF 48TD were isolated and taxonomically characterized from a landfill in Chandigarh, India. The analysis of 16S rRNA gene sequences of the strains confirmed their closest identity to Bacillus thermotolerans SgZ-8T with 99.9% sequence similarity. A comparative phylogenetic analysis of strains 5.5LF 38TD, 5.5LF 48TD and B. thermotolerans SgZ-8(T) confirmed their separation into a novel genus with B. badius and genus Domibacillus as the closest phylogenetic relatives. The major fatty acids of the strains are iso-C15:0 and iso-C16:0 and MK-7 is the only quinone. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. The digital DNA-DNA hybridization (DDH) and ortho average nucleotide identity (ANI) values calculated through whole genome sequences indicated that the three strains showed low relatedness with their phylogenetic neighbours. Based on evidences from phylogenomic analyses and polyphasic taxonomic characterization we propose reclassification of the species B. thermotolerans into a novel genus named Quasibacillus thermotolerans gen. nov., comb. nov with the type strain SgZ-8(T) (=CCTCC AB2012108(T)=KACC 16706(T)). Further our analyses also revealed that B. encimensis SGD-V-25(T) is a later heterotypic synonym of Bacillus badius DSM 23(T).

Investigation into the taxonomy of “ B. aminovorans” and its reclassification to the genus Domibacillus as Domibacillus aminovorans sp. nov. - Verma, Ashish; Ojha, Anup Kumar; Pal, Yash; Kumari, Parveen; Schumann, Peter; Gruber-Vodicka, Harald; Dastager, Syed Gulam; Natarajan, Ramesh Kumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
The species "Bacillus aminovorans" was categorized as species Incertae Sedis meaning taxa with uncertain taxonomic position because of insufficient description of phenotypic properties and lack of understanding of its phylogenetic relationship (Claus and Berkeley [5]). In this study two strains "B. aminovorans" DSM 1314T and DSM 4337 were phenotypically and phylogenomically analyzed. The strains are Gram-staining-positive, spore forming rods and unable to utilize/ferment most of the sugars tested except glucose. The major fatty acids are anteiso-C15:0 and iso-C15:0. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and an aminophosphoglycolipid. The cell wall peptidoglycan is of A1γ type with meso-Dpm as the diamino acid. The menaquinone type present is MK-6. The G+C content of the genomic DNA of the type strain is 40.8mol%. These characteristics were found to be in line with description of the genus Domibacillus. Moreover phylogenetic analysis based on 16S rRNA gene sequence retrieved "B. aminovorans" within the genus Domibacillus with D. antri XD 80T as the closest relative. Additionally genome sequencing of the strains and their comparison with whole genome sequences of other Domibacillus spp. confirmed their distinctiveness and separate species status within the genus based on parameters of genome to genome distance calculator (GGDC) and average nucleotide identity (ANI) values. Therefore a novel species Domibacillus aminovorans sp. nov. (DSM 1314T =LMG 16796T) is proposed.
Keywords: 16S rRNA; Domibacillus aminovorans; MALDI-TOF; ``Bacillus aminovorans''

Taxonomic insights into the phylogeny of Bacillus badius and proposal for its reclassification to the genus Pseudobacillus as Pseudobacillus badius comb. nov. and reclassification of Bacillus wudalianchiensis Liu et al. - Verma, Ashish; Pal, Yash; Ojha, Anup Kumar; Kumari, Munesh; Khatri, Indu; Rameshkumar, N.; Schumann, Peter; Dastager, Syed G.; Mayilraj, Shanmugam; Subramanian, Srikrishna; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2019)
The species Bacillus badius is one of the oldest members of the genus Bacillus isolated from faeces of children and was classified based on its ability to form endospores [8]. In 16S rRNA gene sequence and phylogenetic analysis, Bacillus badius DSM 23(T) shared low similarity (93.0%) and distant relationship with B. subtilis, the type species of the genus Bacillus indicating that it does not belong to this genus. Additional strains of the species, B. badius DSM 5610, DSM 30822 and B. encimensis SGD-V-25 (which has been recently reclassified as a member of this species) were included in the study to consider intraspecies diversity. Detailed molecular phylogenetic and comparative genome analysis clearly showed that the strains of B. badius were consistently retrieved outside the cluster of Bacillus sensu stricto and also distantly related to the genera Domibacillus and Quasibacillus. Further, the data from biochemical reactions (inability to ferment most carbohydrates), polar lipids profile (presence of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an aminophosphoglycolipid) and fatty acids supported the molecular analysis. Thus the four B. badius strains; DSM 23(T), DSM 5610, DSM 30822 and SGD-V-25 displayed sufficient demarcating phenotypic characteristics that warrant their classification as members of a novel genus and single species, for which the name Pseudobacillus badius gen. nov. comb. nov. is proposed with Pseudobacillus badius DSM 23(T) (= ATCC 14574(T)) as the type strain. Additionally, based on our findings from phenotypic, chemotaxonomic and genotypic parameters, Bacillus wudalianchiensis DSM 100757(T) was reclassified as Pseudobacillus wudalianchiensis comb. nov. (C) 2019 Elsevier GmbH. All rights reserved.
Keywords: 16S rRNA; Bacillus; Bacillus wudalianchiensis; Fatty acids; polar lipids; Pseudobacillus

Machine learning-based approach to determine infection status in recipients of BBV152 (Covaxin) whole-virion inactivated SARS-CoV-2 vaccine for serological surveys - Singh, Prateek; Ujjainiya, Rajat; Prakash, Satyartha; Naushin, Salwa; Sardana, Viren; Bhatheja, Nitin; Singh, Ajay Pratap; Barman, Joydeb; Kumar, Kartik; Gayali, Saurabh; Khan, Raju; Rawat, Birendra Singh; et al. (Computers in Biology and Medicine, 2022)
Data science has been an invaluable part of the COVID-19 pandemic response with multiple applications, ranging from tracking viral evolution to understanding the vaccine effectiveness. Asymptomatic breakthrough infections have been a major problem in assessing vaccine effectiveness in populations globally. Serological discrimination of vaccine response from infection has so far been limited to Spike protein vaccines since whole virion vaccines generate antibodies against all the viral proteins. Here, we show how a statistical and machine learning (ML) based approach can be used to discriminate between SARS-CoV-2 infection and immune response to an inactivated whole virion vaccine (BBV152, Covaxin). For this, we assessed serial data on antibodies against Spike and Nucleocapsid antigens, along with age, sex, number of doses taken, and days since last dose, for 1823 Covaxin recipients. An ensemble ML model, incorporating a consensus clustering approach alongside the support vector machine model, was built on 1063 samples where reliable qualifying data existed, and then applied to the entire dataset. Of 1448 self-reported negative subjects, our ensemble ML model classified 724 to be infected. For method validation, we determined the relative ability of a random subset of samples to neutralize Delta versus wild-type strain using a surrogate neutralization assay. We worked on the premise that antibodies generated by a whole virion vaccine would neutralize wild type more efficiently than delta strain. In 100 of 156 samples, where ML prediction differed from self-reported uninfected status, neutralization against Delta strain was more effective, indicating infection. We found 71.8% subjects predicted to be infected during the surge, which is concordant with the percentage of sequences classified as Delta (75.6%-80.2%) over the same period. Our approach will help in real-world vaccine effectiveness assessments where whole virion vaccines are commonly used.
Keywords: BBV152; Covaxin; COVID-19; Ensemble methods; Infection; machine learning; SARS-CoV-2